A novel aqueous micellar two-phase system composed of surfactant and mannitol for purification of polygalacturonase enzyme from Durio zibethinus Murray and recycling phase components - Amid, Mehrnoush; Murshid, Fara Syazana; Manap, Mohd Yazid; Hussin, Muhaini; Sarker, Md. Zaidul Islam; Chong, Gun Hean (Taylor & Francis, 2016)
A novel aqueous micellar two-phase system composed of surfactant and mannitol was employed for the first time to purify polygalacturonase from Durio zibethinus Murray. The influences of different parameters such as type of surfactants, composition of surfactant/mannitol, pH and crude load on polygalacturonase partitioning were investigated. The results indicated that the polygalacturonase was recovered in 25% Tween 80 and 22% mannitol, at 68.2% of Tie line length, crude load of 30% at pH 5.0. The enzyme was successfully recovered with a high purification factor of 16.1 and yield of 97.3% while phase components were also recovered and recycled above 95%.